Semiconductor Photocatalysis - Materials, Mechanisms and Applications 2016
DOI: 10.5772/62637
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser-Deposited TiO2-based Films: Synthesis, Electronic Structure and Photocatalytic Activity

Abstract: Abstract"ctive under visible light, photocatalysts based on doped titania were obtained via pulsed laser deposition PLD method. To find out the crystalline structure, optical properties, and electronic structure, the following techniques such as X-ray diffraction, electronic spectroscopy, electrical conductivity measurements, and X-ray photoelectron spectroscopy XPS are used. Photocatalytic activity is monitored by applying the photoreduction of dichromate ions under UV and visible light. The influence of zirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…XPS values within 396–397 eV are signed to the formation of the bond corresponded to N–Ti–N bonds [27, 28] and O-Ti-N [28, 29], respectively. N1s binding energies of 399.1 and 400.5 eV measured for modified by urea commercially available TiO 2 powder were assigned to carbon nitrides (399–400 eV, C = N-C), graphite-like phases (400.6 eV, N-Csp 2 ) and to polycyanogen (399.0, 400.5 eV, (−C = N−) x ) [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XPS values within 396–397 eV are signed to the formation of the bond corresponded to N–Ti–N bonds [27, 28] and O-Ti-N [28, 29], respectively. N1s binding energies of 399.1 and 400.5 eV measured for modified by urea commercially available TiO 2 powder were assigned to carbon nitrides (399–400 eV, C = N-C), graphite-like phases (400.6 eV, N-Csp 2 ) and to polycyanogen (399.0, 400.5 eV, (−C = N−) x ) [30].…”
Section: Resultsmentioning
confidence: 99%
“…Binding energy positions at 397.2, 398.1, and 399.8 eV provide the assumption about an interstitial nitrogen incorporation with the trace of remained nitrogen-carbon bonds. Analyzing all our previous investigations connected with the nitrogen and metal co-doped titania films, it is concluded that interstitial nitrogen incorporation occurred when urea was applied as the doping agent [31, 32], On the other hand, the substitutional nitrogen incorporation performed by Pulse laser deposition method is responsible for the improvement of photocatalytic performance for nitrogen and zirconia co-doped titania films [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, as the electrons leave the thin, metal oxyhydroxide layer, it depletes, gaining a more positive charge relative to the titania, which in turn allows for a much easier adsorption of the oxygen from the OH − groups ( Figure 14 ). Moreover, laser modification can result in the formation of additional oxygen vacancies within titania, leading to an elevated potential difference in the depleted micro p-n junction [ 69 , 70 ].…”
Section: The Laser-induced Morphological Transformation Of Titania Na...mentioning
confidence: 99%
“…A different approach in creating the buried oxide layers can be provided by a versatile technique, which is pulsed laser deposition (PLD) [9][10][11][12]. This study focuses on the preparation and characterization of silicon-oxide-silicon structures obtained as stacked thin films deposited on silicon wafer by PLD.…”
Section: Introductionmentioning
confidence: 99%